The effect of fatigue on the 200 m front crawl underwaterstroke pattern - Figueiredo, P.; Nazario, R.; Cereja, A.; Vilas-Boas, J. P.; Fernandes, R. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The present study aimed to investigate the effect of fatigue on the spatial underwater swimming arm-stroke pattern. Ten male swimmers performed a 200 m front crawl at maximal intensity. The kinematic stroke parameters recorded by six cameras were: mean swim velocity, stroke length, stroke frequency, and a number of upper limb linear and angular displacements and velocities. Differences between the four laps were assessed with a repeated measure ANOVA and effect sizes. Fatigue effect was shown in the significant decrease of the velocity (swimming and arm), depths and elbow angle at the end of backward movement. The present findings could be useful for coaches in evaluating fatigue effects on the swimming technique.